Feline immunodeficiency virus infection is enhanced by feline bone marrow-derived dendritic cells - van der Meer, F. J. U. M.; Schuurman, N. M. P.; Egberink, H. F. (Journal of General Virology, 2007)
In the pathogenesis of feline immunodeficiency virus (FIV) infection, feline dendritic cells (feDCs) are thought to play an important role. As with DCs in other species, feDCs are believed to transport virus particles to lymph nodes and transfer them to lymphocytes. Our investigation has focused on the ability of feDCs to influence the infection of syngeneic peripheral blood mononuclear cells (PBMCs) and allogeneic thymocytes. feDCs were derived from bone marrow mononuclear cells that were cultured under the influence of feline interleukin-4 and feline granulocyte–macrophage colony-stimulating factor. By using these feDCs in co-culture with resting PBMCs, an upregulation of FIV replication was shown. An enhancement of FIV infection was also detected when co-cultures of feDCs/feline thymocytes were infected. To obtain this enhancement, direct contact of the cells in the co-culture was necessary; transwell cultures showed that the involvement of only soluble factors produced by feDCs in this process is not likely. These feDCs were also able to induce the proliferation of resting thymocytes, which might explain the enhanced FIV replication observed. Together, these data suggest that feDCs have abilities similar to those shown for simian and human DCs in the interaction with leukocytes. This system is suitable for further investigations of the interplay of DC and T cells during FIV infection in vitro.